Uganda - Clarke, Ian, 1952 January 1- (London : Kuperard Publishers, 2015)
Inevitably there are cultural pitfalls for the unwary traveler—differences in expectations, mores, and ways of behaving. This book provides key insights into Ugandan life and offers practical tips on how best to meet the Ugandan people on their own terms, vital information for tourists and businessmen alike. --Publisher
Land and people -- Values and attitudes -- Customs and traditions -- Making friends -- Ugandans at home -- Time out -- Travel, health, and safety -- Business briefing -- Communicating.
Includes bibliographical references (page 165) and index.
Keywords: Uganda -- Guidebooks; Uganda -- Social life and customs -- 21st century; Etiquette -- Uganda; Visitors, Foreign -- Uganda -- Life skills guides